2010
DOI: 10.3109/00016351003752395
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, mechanical and morphological properties of hypomineralized enamel of permanent first molars

Abstract: Teeth diagnosed with molar incisor hypomineralization have significantly lower hardness values in the hypomineralized enamel compared with normal enamel. The hardness values vary according to the morphological and chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
1
26

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 22 publications
12
108
1
26
Order By: Relevance
“…(Xie et al, 2008) These changes appear to occur during enamel maturation and may be responsible for the marked reduction in hardness and elastic modulus of the affected enamel. (Fagrell et al, 2010) In addition, the enamel in the transitional region adjacent to the demarcated defects in MIH has also notable alterations in their prism sheaths. Despite the translucent, normal appearance, the transitional region between the affected and unaffected regions in MIH teeth had weakened prism sheaths which compromised its overall mechanical properties.…”
Section: Characteristics Of Mih Affected Teethmentioning
confidence: 99%
“…(Xie et al, 2008) These changes appear to occur during enamel maturation and may be responsible for the marked reduction in hardness and elastic modulus of the affected enamel. (Fagrell et al, 2010) In addition, the enamel in the transitional region adjacent to the demarcated defects in MIH has also notable alterations in their prism sheaths. Despite the translucent, normal appearance, the transitional region between the affected and unaffected regions in MIH teeth had weakened prism sheaths which compromised its overall mechanical properties.…”
Section: Characteristics Of Mih Affected Teethmentioning
confidence: 99%
“…The affected enamel presents demarcated opacities of different colors, which occasionally undergo post-eruptive breakdown because of enamel porosity, 4 leading to results ranging from mild atypical cavities to severe coronary destruction 4,5,6 that may require a more in-depth MIH diagnosis and preventive treatment with fluoride and sealants in patients affected by MIH. 6,7 The studies have suggested that FPMs affected by MIH are more susceptible to dental caries than non-affected Camila Maria Bullio FRAGELLI (a) Juliana Feltrin de SOUZA (b) Diego Girotto BUSSANELI (a) Fabiano JEREMIAS (a) Lourdes dos SANTOS-PINTO (a) Rita de Cássia Loiola CORDEIRO (a) teeth, mainly because of the lower resistance to caries lesion and enamel fracture, which can lead to enamel breakdown.…”
Section: 23mentioning
confidence: 99%
“…The HG group included FPMs with MIH of mild severity that presented white, yellow, and brown opacities, and that showed both mechanical and chemical alteration of the enamel, 4 consequently being at a high risk for carious lesion or breakdown. 6,7,9 The exclusion criteria for both groups included FPMs with cavitated carious lesions or fixed orthodontic appliances, FPMs classified as having severe MIH, presenting enamel breakdown, or FPMs with other enamel malformations linked to specific syndromes and/or dental fluorosis.…”
Section: Subjectsmentioning
confidence: 99%
“…Osnovni patogenetski mehanizam MIH je poremećaj resorptivnog potencijala ameloblasta i inhibicija proteolitičkih enzima usled čega dolazi do zadržavanja gleđnih proteina, ometanja rasta kristala i maturacije gleđi [9][10][11][12][13][14] . Rezultat toga je promena u mineralnom sastavu gleđi, povećanje poroznosti, smanjenje tvrdoće i modula elastičnosti hipomineralizovane gleđi u odnosu na gleđ koja nije zahvaćena promenama, što se klinički manifestuje promenama u boji gleđi, koje variraju od beličastih do promena braon prebojenosti [15][16][17] . Osim toga, utvrđeno je da hipomineralizovana gleđ ima 3-15 puta veći sadržaj proteina u odnosu na normalnu gleđ.…”
Section: Uvodunclassified
“…The main pathogenic mechanism of MIH is the disorder of adsorbent potential of ameloblasts and inhibition of proteolytic enzymes, causing retention of enamel proteins, interfering with crystal growth and maturation of enamel [9][10][11][12][13][14] . This results in the transformation of mineral composition of the enamel, increase in porosity, decrease in hardness and elasticity module of hypomineralized enamel compared to the nonaffected enamel, which is clinically manifested by changes in enamel colour that varies from whitish to changes of brown discoloration [15][16][17] . Besides, it is established that hypomineralized enamel had 3-15fold higher protein content than the normal enamel.…”
Section: Introductionmentioning
confidence: 99%